(untitled) (Journal of Atomic and Molecular Sciences, 2010)
We discuss the blinking statistical behaviors of dynamics of single molecule system, using the recently developed generating function method. We make a thorough study of the fluorescence blinking behaviors and get the statistical properties of the jumping events respectively onto ON state or OFF state, such as the waiting time and waiting time distribution for every directional jumping event, the cumulants of jumping events, the cross correlation, the joint probabilities between two directional jumping events and the probabilities.